In Defense of the Moral Significance of Empathy - Simmons, Aaron (Ethical theory and moral practice, 2014)
It is commonly suggested that empathy is a morally important quality to possess and that a failure to properly empathize with others is a kind of moral failure. This suggestion assumes that empathy involves caring for others’ well-being. Skeptics challenge the moral importance of empathy by arguing that empathy is neither necessary nor sufficient to care for others’ well-being. This challenge is misguided. Although some forms of empathy may not be morally important, empathy with another’s basic well-being concerns is both necessary and sufficient to care for another’s well-being, provided that one’s empathy is both cognitive and affective. I further defend the idea that empathy of this form is a moral virtue. In doing so, I address three challenges to empathy’s status as a virtue: (1) that empathy is unnecessary for being ethical, (2) that it is not useful for promoting ethical behavior, and (3) that an empathetic person can lack other traits central to being virtuous, such as being motivated by the moral good and being disposed to do virtuous things whenever appropriate opportunities arise. I argue that these challenges are mistaken.